The Influence of Cooperative Integrated Reading and Composition Model on Completing Abilities of Story Questions - Muhammad Ridhollah; Muliana Muliana; Mursalin Mursalin (Malikussaleh Social and Political Reviews, 2021)
This study is motivated by the low ability of students in solving story problems at MTsN 4 Aceh Utara. Based on initial observations, students have not been able to understand the story questions, namely determining what is known and asked, students have not been able to determine the formula or method used, and students have not been able to determine the final answer to the story questions, therefore this study aims to determine the effect of Cooperative Integrated Reading and Composition learning model on the ability to solve story problems in class VIII MTsN 4 Aceh Utara. This study uses a quantitative approach with a quasi-experimental research design and a posttest-only design with nonequivalent groups. The population of this study was all students of class VIII MTsN 4 North Aceh. The sample in this study was class VIII C as the control class and class VIII D as the experimental class which was obtained by purposive sampling technique. The data collection technique used in this study is a test in the form of a posttest. Data analysis was carried out to test the ability to solve story problems using the t-test because the data were normally distributed and homogeneous, the data was processed using SPSS 18 software. The normality test used the Shapiro Wilk technique, the homogeneity test used the Levene test, and the hypothesis test according to the test criteria was if significant <0.05, then H0 is rejected and Ha is accepted, whereas if the significant value is 0.05, then H0 is accepted and Ha is rejected. From the statistical significant results, Equal Variances assumed is 0.00 less than 0.05. Thus, the conclusion of this study is that there is an effect of the Cooperative Integrated Reading and Composition learning model on the ability to complete stories in class VIII MTsN 4 Aceh Utara.